2010
DOI: 10.1159/000314365
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aerosol and Intranasal Challenge in a Mouse Model of Allergic Airway Inflammation and Hyperresponsiveness

Abstract: Background: The aim was to optimize antigen challenge for induction of airway hyperresponsiveness (AHR) and inflammation in BALB/c mice sensitized to ovalbumin (OVA). Comparisons were made between mice challenged with OVA either as an aerosol or intranasally. The protocol that induced maximal AHR in BALB/c mice was thereafter tested in C57BL/6 mice. Method: Methacholine responsiveness was measured using the flexiVent® system to assess AHR. Inflammatory responses were investigated by histology and cell counts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 55 publications
3
30
0
4
Order By: Relevance
“…Similar to the results from our current study, mice that were challenged by intranasal delivery with Burkholderia pseudomallei also showed a high incidence of meningitis [80]. In addition, other studies have shown differences between intranasal or aerosol delivery in dissemination of bacterial pathogens [80], [81] or inflammation response to allergens [82] in mice.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the results from our current study, mice that were challenged by intranasal delivery with Burkholderia pseudomallei also showed a high incidence of meningitis [80]. In addition, other studies have shown differences between intranasal or aerosol delivery in dissemination of bacterial pathogens [80], [81] or inflammation response to allergens [82] in mice.…”
Section: Discussionsupporting
confidence: 90%
“…Sensitisation and subsequent intranasal challenge with OVA is a well-established model to induce allergic lung inflammation in rodents [20], [21]. In this study, our protocol was shown to mimic prototypical characteristics of clinical atopic asthma, namely blood, tissue and BALF eosinophilia, an elevation of TH2 cytokines IL-5 and IL-13 in BALF, and prominent AHR, as shown by a heightened reactivity to methacholine.…”
Section: Discussionmentioning
confidence: 81%
“…Following anesthesia with pentobarbital (70 mg/kg body wt ip), the pulmonary mechanics of the mice were assessed as described previously (37). Using the forced-oscillation technique, lung resistance was determined assuming a single compartment linear model.…”
Section: Methodsmentioning
confidence: 99%